Moving from research to practice: relevance and generalizability - Diederick E Grobbee (Jurnal Kardiologi Indonesia, 2008)
Epidemiology is occurrence research. The object of epidemiologic research is the occurrence of illness and its relation to determinants (occurrence relation). Similar to other epidemiologic research, the motive for applied clinical studies is to learn about an object. Eventually, the knowledge produced by the research needs to be incorporated in the knowledge base that guides daily medical care. During the design and conduct of research, it is important to keep this aim in mind and be aware of the effects that choices in the design of the study may have on the applicability and implementation of the results.